PENERAPAN METODE MAKE A MATCH BERBASIS PANCINGAN KATA UNTUK MENINGKATKAN KEMAMPUAN MENULIS BAHASA ARAB - Shalihah, Hanifa Hasna (ALSUNIYAT: Jurnal Penelitian Bahasa, Sastra, dan Budaya Arab, 2018)
The study was conducted with the aim to find out how the application of the method of making a match based on word provocation to improve the ability to write Arabic in students. This research is a quasi-experimental study with research subjects of VIII grade students of Miftahul Junior High School in Bandung. Data obtained by conducting tests, observations, and interviews with instruments in the form of essay test questions, observation guidelines, and interview guidelines. The collected data were analyzed using quantitative data analysis. The results of this study indicate that 1) at this stage the learning process using the make a match method begins with the presentation of Arabic text contained in the material. 2) improvement in learning outcomes of writing skills through the application of the make a match method can be seen in students' writing ability to increase. 3) student learning outcomes using the make a match method have increased with an average value of 86 with the number of students who have completed learning as much as 95%.